Bioinformatic analysis of circular RNA expression profiles in a rat lumbosacral spinal root avulsion model - Zhou, Zhibin; Ma, Jun; Cai, Jiao; Chen, Aimin; Zhu, Lei (Frontiers in Genetics, 2022)
Lumbosacral spinal root avulsion (LSRA) is a severe nerve injury that results in devastating dysfunction in the lower limb. Circular ribonucleic acids (circRNAs) have been reported to be implicated in a variety of diseases. However, the role of circRNAs in LSRA remains unclear. Here, we performed RNA sequencing (RNA-seq) to determine circRNA expression profiles in a rat LSRA model and further investigated their potential functions and the underlying mechanisms by bioinformatic analyses and in vitro experiments. In all, 1708 circRNAs were found to be differentially expressed in spinal cord tissues after LSRA (|fold change| ≥ 2 and p < 0.05), with 591 up-regulated 1117 down-regulated. Meanwhile, 2263 mRNAs were also indentified to be differentially expressed, of which 1471 were upregulated and 792 were downregulated. Eight randomly selected circRNAs and mRNA were successfully verified to be consistent the RNA-seq results by quantitative real-time polymerase chain reaction. Functional analyses based on gene ontology and Kyoto Encyclopedia of Genes and Genomes predicted the potential roles of differentially expressed circRNAs and mRNAs in LSRA, and circRNA/miRNA/mRNA interaction networks revealed that circRNA_7025, a down-regulated circRNA in LSRA, was targeted by two neuronal apoptosis-related miRNAs, rno-miR-1224 and rno-miR-326-5p. Further in vitro experiments revealed that circRNA_7025 protected against oxygen-glucose deprivation induced neuronal apoptosis via the circRNA_7025/miR-1224/miR-326-5p axis. In summary, our results revealed circRNA expression profiles and their potential functions in LSRA. These findings improve our understanding of the pathogenic mechanisms involved in LSRA and might enable us to identify new molecular targets for LSRA.